2007
DOI: 10.1897/07-519
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Analysis of Endocrine Disrupting Hormones and Estrogenic Activity in an Advanced Sewage Treatment Plant

Abstract: The steroid hormones estrone (E(1)), 17beta-estradiol (E(2)), estriol (E(3)), 17alpha-ethinylestradiol (EE(2)), and their conjugated forms were surveyed throughout an advanced sewage treatment plant (STP). The estrogen concentrations in water and sludge samples, collected in October 2004 and April 2005, were determined by gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry. Simultaneously, the estrogenic activity was quantified using estrogen-responsive reporter cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 23 publications
5
43
0
3
Order By: Relevance
“…Control and BPAexposed females exhibited longer duration of nose-to-nose contact (mean ± SEM) with control males than with BPA-exposed males. *P < 0.05. of species (39,(50)(51)(52), masculinized their spatial abilities and exploratory behaviors and led to a phenotype more similar to that of control males than control females. Laboratory mice (Mus musculus domesticus) and rats (Rattus norvegicus) exposed during prenatal through postnatal development to EE similarly demonstrate increased male-like patterns of behavior, and as in deer mice, a similar regimen of BPA exposure did not induce comparable responses (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Control and BPAexposed females exhibited longer duration of nose-to-nose contact (mean ± SEM) with control males than with BPA-exposed males. *P < 0.05. of species (39,(50)(51)(52), masculinized their spatial abilities and exploratory behaviors and led to a phenotype more similar to that of control males than control females. Laboratory mice (Mus musculus domesticus) and rats (Rattus norvegicus) exposed during prenatal through postnatal development to EE similarly demonstrate increased male-like patterns of behavior, and as in deer mice, a similar regimen of BPA exposure did not induce comparable responses (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys in full-scale WWTPs have indicated that plants with a high SRT generally showed high and stable removal of both estrogens and estrogenic activity (Hashimoto et al, 2007;Muller et al, 2008). With regard to natural estrogens, Clara et al (2005) have observed a strong correlation between achievable effluent concentrations and SRT.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of chemical substances found in wastewater to interact with the estrogen receptor (ER) has been recognized for several years [1,[6][7][8]. In these reports, the estrogenic activity of municipal STP effluents varied from 0.4 to 2.4 ng/L 17b-estradiol (E2) equivalents in different assays [1,8].…”
Section: Introductionmentioning
confidence: 99%